Comparative Analysis of Smart Catalysts for CO? Reduction: From Molecular Design to Lab-Scale Performance - Nampira, Ardi Azhar; Mendes, Clara; Costa, Tiago (Research of Scientia Naturalis, 2025)
The electrochemical reduction of carbon dioxide (CO?) is a critical strategy for mitigating climate change and producing value-added chemicals, yet the development of highly selective catalysts remains a primary challenge. This study aimed to conduct a rigorous comparative analysis of three distinct classes of "smart" catalysts—a molecular cobalt complex, a metal-organic framework (MOF), and a single-atom copper catalyst (Cu-SAC)—to elucidate the relationship between molecular design and lab-scale performance. The catalysts were synthesized, characterized via XRD and XAS, and evaluated for electrocatalytic CO? reduction in a flow cell reactor. The results showed that the Cu-SAC exhibited superior performance, achieving a Faradaic efficiency for ethylene (C?H?) exceeding 70% at a low cell voltage, significantly outperforming the MOF and molecular catalysts, which primarily produced CO and formate. This high selectivity was directly correlated with the optimized coordination environment of the isolated Cu sites. This comparative analysis confirms that rational design at the atomic level is a highly effective strategy for steering reaction pathways towards valuable multi-carbon products, providing a crucial benchmark for future catalyst development.